La experiencia mexicana de Charles Wright Mills - Servín, Elisa (El Colegio de México, A.C., 2020)
In early 1960, the U.S. sociologist C. Wright Mills visited Mexico to give a seminar at the unam. There he met a group of intellectuals who, like him, were interested in the reconstruction of the left. Their enthusiastic solidarity with the Cuban Revolution ended up having a major effect on Mills. It argues that his discussions with Carlos Fuentes, Enrique González Pedrero, Víctor Flores Olea, Jaime García Terrés and Pablo González Casanova, among others, led him to travel to Cuba in order to understand that country’s revolutionary process, which was the subject of a major debate in the international left. His visit to the island would result in his famous book Listen, Yankee, which would become a best-seller in the United States, with hundreds of thousands of copies sold in a matter of weeks. A few months later, the Fondo de Cultura Económica published the book in Spanish. Escucha, Yanqui would be the top-selling book of 1961 and became required reading for the Latin American New Left. By studying the correspondence between Mills, Carlos Fuentes and Arnaldo Orfila Reynal, this article reconstructs the gestation process for this book, which would be the most concrete result of the encounter between Mills and his Mexican friends.